“Conks” as Memory of the Holy Word: A Ritual and Literary Analysis of a “Conk” Concerning Alevi Practice (Journal of Alevism-Bektashism Studies, 2016)
“Conks” which have an important place in Turkish culture and literature, show a unique structure within Alevi writing tradition. In this sense, it occurs that the contents of “conks” belonging to “dedes” and “zakirs”, are organized in accordance with ritual practices known as Twelve Services performed within “cems” which are the most important ritual of Alevi belief system. From this aspect, “conks” have a ritual value along with cultural and literary values within Alevi belief system. This characteristic of “conks” belonging to Alevi authors provides important suggestions directed to the clarification of ritual performance in the past years, as a result of comparison of ritual and oral tradition with `writing tradition. In this paper, ritual aspects related to Alevi writing tradition and “conks”, were analyzed on the sample of a “conk” belonging to Dervish Seyit Ali member of Diyarbakir wing of the Aguicen “ocak”, who lived in the second half of the 19th century. This “conk” which contains examples of “deyish”, “duvaz imam”, “nutuk”,“tevhit”, “mersiye” and “miraclama” types performed in the past years within “cem” rituals of communities connected to Alevi “ocaks” of Diyarbakir province, is quite important in terms of clarification of poetical performances regarding rituals. The fact that many poetical texts concerning “cem” rituals which are about to be forgotten and were recorded within our field work, are in this conk increases the importance of comparative analysis between the conk and oral tradition in terms of ritual and literature. Besides, when taken in account that in Alevi writing tradition practice books and “conks” belonging to “dedes” are usually organized and classified by ritual structure, the importance of this kind of comparison and analysis will be better understood. Within this scope, functional characteristics of the poetical texts in the conk, which is the subject of our paper, within ritual are analyzed comparatively with oral tradition and other written sources concerning place of the texts in the ritual structure and types of poems. As for the second stage of the research, there will be presented the results obtained in the wake of literary analysis of the form and content of poems included in the “conk”.